Bridges tested to failure in Sweden - Täljsten, Björn; Blanksvärd, Thomas; Sas, Gabriel; Bagge, Niklas; Nilimaa, Jonny; Popescu, Cosmin; Elfgren, Lennart; Carolin, Anders; Häggström, Jens (Luleå tekniska universitet, Byggkonstruktion och brand, 2018)
Five bridges of different types have been tested to failure and the results have been compared to analyses of the load-carrying capacity using standard code models and advanced numerical methods. The results may help to make accurate assessments of similar existing bridges. There it is necessary to know the real behaviour, weak points, and to be able to model the load-carrying capacity in a correct way.The five bridges were: (1) a strengthened one span concrete road bridge - Stora Höga (2) a one span concrete rail trough bridge loaded in fatigue – Lautajokk; (3) a two span strengthened concrete trough railway bridge - Övik; (4) a one span railway steel truss bridge -Åby; and (5) a five span prestressed concrete road bridge - Kiruna. The unique results in the paper are the experiences of the real failure types, the robustness/weakness of the bridges, and the accuracy and shortcomings/potentials of different codes and models for safety assessment of existing structures ISBN för värdpublikation: 978-1-5108-9208-8